Antiretroviral Medicine Ethical Execution Policy for HIV / AIDS Survivors in Indonesia - Aga Natalis; Sukimin; Tri Mulyan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: One of the health problems in Indonesia that has not been resolved is the HIV pandemic orHuman Immunodeficiency Virus or a virus that attacks/infects white blood cells which causes a decrease inhuman immunity. To combat HIV/AIDS, treatment is performed through antiretroviral drugs. But in fact,antiretroviral drugs are often scarce which causes a decrease in the welfare of people with HIV / AIDS inIndonesia.Research Objectives: This study aims to discover and analyze some policies on administering antiretroviraldrugs that are fair for people with HIV/AIDS in Indonesia.Methods: This study uses a qualitative method with a normative juridical approach. The data used aresecondary data consisting of primary and secondary legal materials. The data was collected through aliterature study and analyzed qualitatively.Conclusion: In making policies, the implementation of antiretroviral drugs must be centered on PLWHAand use the PLWHA as policy actors. The policy of delivering ARV drugs that are centered on PLHIVis expected to produce fair policy outputs and then have implications for the high welfare of PLWHA inIndonesia, this is in line with the formation of a policy based on the study of responsive legal theory initiatedby Nonet and Selznick. Responsive legal theory requires that the law that has implications for PLWHA,should always be sensitive to the needs of PLWHA, especially regarding the availability of ARV drugs.